2000
DOI: 10.1021/om9909993
|View full text |Cite
|
Sign up to set email alerts
|

ansa-Chromocene Complexes. 1. Synthesis and Characterization of Cr(II) Carbonyl andtert-Butyl Isocyanide Complexes

Abstract: ansa-Calcocene compounds are effective reagents for the synthesis of ansa-chromocene complexes from CrCl 2 in the presence of a trapping ligand such as carbon monoxide or an isonitrile. A variety of ansa-chromocene carbonyl and tert-butyl isocyanide complexes have been prepared in this manner in high yields. The X-ray crystal structure of one of these complexes,CrCO, is described. Electrochemical studies on these complexes show that the isonitrile derivatives are more easily oxidized than the carbonyl derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…In fact, the CO ligand is required to stabilize the 16 e ansa-chromocene fragment. Improved synthetic routes to 1 and related isocyanide derivatives [6][7][8] …”
Section: }]mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the CO ligand is required to stabilize the 16 e ansa-chromocene fragment. Improved synthetic routes to 1 and related isocyanide derivatives [6][7][8] …”
Section: }]mentioning
confidence: 99%
“…Improved single-point energies were obtained at the b3-lyp/TZVPP level and solvent corrections were calculated using the cosmo solvation model (e = 7.5, THF). Frequency calculations were not feasible for the larger systems, so all energies discussed below are elec- [7].…”
mentioning
confidence: 99%
“…They do, however produce a mixture of rac and meso stereoisomers that can be readily separated by crystallization (Eqn 4). Ansa-chromocene carbonyl and t-butylisocyanide complexes 3-6 were isolated in 60-80% yields [67] as compared with 30-50% yields for 1 and 2 (Eqn 5).…”
Section: Ansa-chromocene Compounds Two Atom-bridged Ansa-chromocene Cmentioning
confidence: 99%
“…We too performed cyclic voltammetry measurements on complex 1 and other ansa-chromocene carbonyl and isocyanide derivatives [67,71]. Some interesting trends are worth noting from the data in Table 1.…”
Section: Cr(ii) Cr(iii)mentioning
confidence: 99%
“…Whereas the carbonyl complex Cp 2 CrCO cannot be isolated due to the reversible binding of CO by chromocene [8], various ansa-chromocenes were prepared and crystallographically characterized [9,10]. DFT calculations indicated that the stabilization of the CO complex of ansa-chromocene is the consequence of the stability of the triplet metallocene product.…”
Section: Introductionmentioning
confidence: 99%